2023
DOI: 10.1039/d3dt00261f
|View full text |Cite
|
Sign up to set email alerts
|

Stable single phases of samarium gallium oxide (Sm3GaxOy) nano semiconductor self-assembly for supercapacitor and photocatalytic applications

Abstract: A cutting-edge approach has been attempted in the present work to develop two stable phases of samarium gallium oxide as functional materials in the form of energy storage electrodes and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…59 The specific capacity of the electrode materials was calculated from the GCD process using eqn (2) and (3).here, “ C ” refers to specific capacity (C g −1 and mA h g −1 ), where “ i ”, “Δ t ”, “ m ”, and “Δ V ” indicate current density (A), discharge time (s), the mass of the active material (g), and applied potential (V), respectively. 60 The calculated values of the specific capacity for NiV 2 O 6 , Ni 2 V 2 O 7 , and Ni 3 V 2 O 8 are 251 C g −1 (69.7 mA h g −1 ), 192.3 C g −1 (53.4 mA h g −1 ), and 207.3 C g −1 (57.52 mA h g −1 ) at 1 A g −1 , respectively. The fabricated electrodes have a larger specific capacity at low current densities, which supports the ion exchange process.…”
Section: Resultsmentioning
confidence: 99%
“…59 The specific capacity of the electrode materials was calculated from the GCD process using eqn (2) and (3).here, “ C ” refers to specific capacity (C g −1 and mA h g −1 ), where “ i ”, “Δ t ”, “ m ”, and “Δ V ” indicate current density (A), discharge time (s), the mass of the active material (g), and applied potential (V), respectively. 60 The calculated values of the specific capacity for NiV 2 O 6 , Ni 2 V 2 O 7 , and Ni 3 V 2 O 8 are 251 C g −1 (69.7 mA h g −1 ), 192.3 C g −1 (53.4 mA h g −1 ), and 207.3 C g −1 (57.52 mA h g −1 ) at 1 A g −1 , respectively. The fabricated electrodes have a larger specific capacity at low current densities, which supports the ion exchange process.…”
Section: Resultsmentioning
confidence: 99%
“… 42 Sm 3 Ga x O y (samarium gallium oxide) is a complex material system; depending upon the composition and synthesis conditions, this can have multiple phases. 43 A cutting-edge development has been attempted by Shanmugam et al for the synthesis of two stable phases of samarium gallium oxide for photosynthesis and energy storage electrodes. A gel matrix method has been adopted for the synthesis of two stable phases, as represented in Fig.…”
Section: Application Of Gallium-based Materials Towards Supercapacitorsmentioning
confidence: 99%
“…Finally, it was concluded that the both phases of samarium gallium oxide have the potential for energy storage and environmental remediation applications. 43 …”
Section: Application Of Gallium-based Materials Towards Supercapacitorsmentioning
confidence: 99%